Proceedings of Data Analytics and Management ICDAM 2024, Volume 5 - Swaroop, Abhishek; Virdee, Bal; Correia, Sérgio Duarte; Polkowski, Zdzislaw (Lecture Notes in Networks and Systems, 2025)
XX, 753 p. 299 illus., 259 illus. in color.